Piece work pay and hourly pay over the cycle - Robert A. Hart (Institute for the Study of Labor (IZA), 2006)
This paper investigates the relative cyclical behavior of the pay of piece workers and hourly paid workers. It uses a unique data set of blue-collar workers in British engineering between 1926 and 1966. The statistics are obtained from the payrolls of firms belonging to the Engineering Employers Federation (EEF). Roughly, the EEF accounted for one-third of the total engineering workforce. The data consist of cell averages delineated by 15 occupations in 29 engineering districts. Via a firm-union bargaining modelling structure, the question is examined as to likely earnings responses to price shocks under the two payment systems. The empirical work entails testing for cyclical differences in the two payments methods Insights are gained from distinguishing between the relatively tight post-war and slack pre-war labor markets.
Keywords: E32; J31; J33; 330; piece work pay; hourly pay; business cycle; Akkordlohn; Zeitlohn; Maschinenbau; Konjunktur; Großbritannien